2008
DOI: 10.2460/javma.232.12.1834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orally administered tramadol alone or with an intravenously administered opioid on minimum alveolar concentration of sevoflurane in cats

Abstract: OBJECTIVE-To compare the effect of oral administration of tramadol alone and with IV administration of butorphanol or hydromorphone on the minimum alveolar concentration (MAC) of sevoflurane in cats. DESIGN-Crossover study. ANIMALS-8 Healthy 3-year-old cats. PROCEDURES-Cats were anesthetized with sevoflurane in 100% oxygen. A standard tail clamp method was used to determine the MAC of sevoflurane following administration of tramadol (8.6 to 11.6 mg/kg [3.6 to 5.3 mg/lb], PO, 5 minutes before induction of anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…33 Larger tramadol doses ranging between 11 and 80 mg/kg (5.0 and 36.36 mg/lb) were used safely for studies in cats and rodents. 13,34 Because of limited clinical experience with tramadol in reptiles, a wide range of doses (1 to 25 mg/kg) were used in the present study to test antinociception in turtles. In mammals, the analgesic effects of tramadol typically begin within 30 minutes and last for 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…33 Larger tramadol doses ranging between 11 and 80 mg/kg (5.0 and 36.36 mg/lb) were used safely for studies in cats and rodents. 13,34 Because of limited clinical experience with tramadol in reptiles, a wide range of doses (1 to 25 mg/kg) were used in the present study to test antinociception in turtles. In mammals, the analgesic effects of tramadol typically begin within 30 minutes and last for 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The transient hypotension (SAP, approx 60 mm Hg) that was evident in 3 rabbits immediately after tramadol administration was unlikely to have affected the MAC. 19 The studies 17,19 in rats and cats involved the tail-clamping technique as the noxious stimulus, but plasma tramadol and M1 concentrations were not reported. 14,26 In the rabbits of the study reported here, IV administration of tramadol at a dose of 4.4 mg/kg resulted in mean plasma tramadol and M1 concentrations of 346 ng/mL and 41 ng/mL, respectively, and a reduction in ISOMAC of 9%, compared with the value before tramadol administration.…”
Section: Discussionmentioning
confidence: 99%
“…In another study 16 involving dogs, when tramadol was administered via a constant rate IV infusion of 1.3 mg/kg/h or 2.6 mg/kg/h, the resulting plasma concentrations of tramadol (2,201 ± 1,552 ng/mL and 4,446 ± 3,875 ng/mL, respectively) and M1 (57 ± 18 ng/mL and 86 ± 20 ng/mL, respectively) caused a reduction in ISOMAC of 26% to 36% when a noxious electrical stimulus was used, although this change was not correlated with plasma tramadol or M1 concentration. 17,19 The M1 metabolite reportedly has a considerable analgesic effect in humans attributable to its action at opioid receptors, 2 but there are several tramadol metabolites that could be responsible for its ISOMAC-lowering effects. Administration of a constant rate infusion of tramadol following the bolus injection may have reduced some of this variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004; Ferreira et al. 2009) and hydromorphone, tramadol and butorphanol decrease the MAC of sevoflurane (Ko et al. 2008).…”
Section: Introductionmentioning
confidence: 99%